2015
DOI: 10.1016/j.eurpsy.2014.09.417
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical industry interactions of psychiatric trainees from 20 European countries

Abstract: There are frequent interactions between European psychiatric trainees and the PI, with significant variation between countries. We identified several factors affecting this interaction, including attribution of an educational role to the PI. Creating alternative educational opportunities and specific training dedicated to PI interactions may therefore help to reduce the impact of the PI on psychiatric training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…It has been shown that contact with pharmaceutical companies should be limited in order to obtain prescribing treatment based on scientific evidence (37). In the Croatian Health Care system, pharmaceutical companies frequently send their representatives to meet with physicians (38). There is a Contract from 2010 on ethical marketing aimed towards regulating contacts between representatives of pharmaceutical companies and physicians, but it is not known what the effects of this Contract are (39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that contact with pharmaceutical companies should be limited in order to obtain prescribing treatment based on scientific evidence (37). In the Croatian Health Care system, pharmaceutical companies frequently send their representatives to meet with physicians (38). There is a Contract from 2010 on ethical marketing aimed towards regulating contacts between representatives of pharmaceutical companies and physicians, but it is not known what the effects of this Contract are (39).…”
Section: Discussionmentioning
confidence: 99%
“…The role and impact of the pharmaceutical industry on prescription patterns has been increasingly debated and several surveys have given researchers interesting insights into this subject 1. A recent systematic review2 reports about 29 studies looking at the impact of visits of drug representatives (reps).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, a national survey demonstrated that more than half of early physician trainees had received a gift of some form from a representative, while over a third had attended industry‐sponsored education sessions . In Europe, a cross‐sectional analysis of psychiatry trainees in 20 countries showed the mean number of encounters with representatives ranged from once to 20 times a month . This is important as doctors‐in‐training are at a particularly vulnerable stage of their careers with regard to developing relationships with the pharmaceutical industry.…”
mentioning
confidence: 99%
“…4 In Europe, a cross-sectional analysis of psychiatry trainees in 20 countries showed the mean number of encounters with representatives ranged from once to 20 times a month. 5 This is important as doctors-in-training are at a particularly vulnerable stage of their careers with regard to developing relationships with the pharmaceutical industry. Residents have been shown in the United States to have little knowledge regarding these relationships, 6 and poor insight into the ramifications of their interactions with pharmaceutical representatives on patient care.…”
mentioning
confidence: 99%